The Dialectics of the Principle of Legality and Living Law in the National Criminal Law System Post-Enactment of Law No. 1 of 2023 - Toatubun , Najarudin; Djamaludin, Djamaludin (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
Indonesia's criminal law system has entered a new phase with the enactment of Law No. 1 of 2023 on the Criminal Code. A key change is the recognition of living law as a source of criminal law alongside statutory regulations. This shift sparks debate over how to harmonize the principle of legality, the cornerstone of the Criminal Code, with the evolving nature of living law. This study examines the interaction between the principle of legality and living law in Indonesia's criminal justice system using a normative juridical method and statutory and conceptual approaches. The study highlights three key aspects: the background of living law recognition, the integration of the principle of legality with living law, and the impact of this integration on law enforcement. The findings reveal that incorporating living law into the new Criminal Code marks a transition from a rigid system to one more attuned to societal needs. However, challenges remain in aligning written law with customary law. These challenges include identifying valid living law, setting clear application boundaries, and regulating customary sanctions within the national legal framework.